Differences between U 18 and U 20 rowers in cardio pulmonary exercise testing on rowing ergometer - Ivišic, A. K.; Spasic, M.; Pavlinovic, V. (3rd International Conference on Science and Medicine in Aquatic Sports Proceedings, 2025)
The aim of this study was to examine physiological differences of aerobic capacities between U 18 a nd U 20 rowers.